A comparative study of catalytic behaviors of Mn, Fe, Co, Ni, Cu and Zn–Based catalysts in steam reforming of methanol, acetic acid and acetone. (4th February 2020) - Li, Jiaojiao; Mei, Xueli; Zhang, Lijun; Yu, Zhenjie; Liu, Qing; Wei, Tao; Wu, Weibing; Dong, Dehua; Xu, Leilei; Hu, Xun
Abstract: This study investigated the distinct catalytic behaviors of mono Mn, Fe, Co, Ni, Cu and Zn catalysts in the reforming of the small organics including methanol, acetic acid and acetone. The results showed that Mn, Fe or Zn-based catalysts showed almost no activity for steam reforming of either methanol, acetic acid or acetone, due to their low capacity to break the chemical bonds of the organics or to activate steam. Co and Cu-based catalysts were generally active for steam reforming of methanol. Nevertheless, Co-based catalysts promoted methanol decomposition to form a substantial amount of CO. Alumina as a support remarkably influenced catalytic stability of the catalyst. The unsupported Cu catalyst showed a much lower stability than Cu/Al2 O3 . Nevertheless, the unsupported Ni was more stable than Ni/Al2 O3 catalyst, due to its high resistivity towards coking. The unsupported Co, however, was prone to coking. The C/H ratios in the coke formed over the unsupported and alumina-supported Ni or Co catalysts were distinct, indicating the involvement of alumina in the coking process. In addition, Ni and Co catalysts behaved differently. Ni/Al2 O3 showed a superior stability than Co/Al2 O3 in steam reforming of acetone. The coke formed on Ni/Al2 O3 was more aromatic than that over Co/Al2 O3 catalysts while morphologies of coke (nanotubes over Ni/Al2 O3 versus fibrous coke over Co/Al2 O3 ) were also different. Highlights: Ni and Co catalysts showed superior activity for reforming than Mn, Fe or Zn. Unsupported Ni was more stable than Ni/Al2 O3, due to high resistivity to coking. Coke formed in acetone reforming was less aromatic than that of acetic acid. Coke formed in Ni and in Ni/Al2 O3 was different due to the effects of alumina. The coke on Ni/Al2 O3 was less aliphatic than on Co/Al2 O3 in acetone reforming.